Geometric and Computer Modeling of Building Structures Forms - Vorontsov, Oleg; Tulupova, Larissa; Vorontsova, Iryna (International Journal of Engineering and Technology, 2018)
The current state of designing curvilinear objects of architecture and construction needs to take into account as many data and requirements as possible to ensure an appropriate model accuracy. In geometric modeling initial data, as a rule, are geometric characteristics and conditions, which are represented in numerical form (coordinates or values of parameters) with quite big arrays. In these conditions, methods of global continuous modeling with a single solution become ineffective. Because of this they require a usage of rather complicated mathematical algorithms and can not provide a necessary adequacy of models. Methods of discrete geometric modeling are free from these drawbacks.The purpose of this article is expanding possibilities of the classical finite difference method and the static-geometric method by applying a geometric apparatus of superposition. In discrete modeling of geometric images this allows using hyperbolic functions as interpolators.The result of this study is a computational template for continuous two-dimensional discrete interpolation. This allows to model geometric images of architectural and building constructions in the form of discrete frames of chain lines.Â Â Â